PATOMORFOLOGІCAL CHANGES OF RAT’S RETINA IN TYPE 2 STREPTOZOTOCIN DІABETІ AFTER INTRODUCTION OF CRYOPRESERVED MESENCYYMAL STEM CELLS OF PLACENTA - Дьомін, Ю.А.; Дьоміна М. Ю. (World of Medicine and Biology, 2015)
In the experiment on the model of streptozotocin-induced type 2 diabetes studied the morphology of the retina after the use of cryopreserved mesenchymal stem cells of the placenta. Tereapevticheskaya prove the efficacy of cryopreserved placental mesenchymal stem cells, which expressed decrease swelling and decrease of apoptotic and destructive manifestations in the retina.